Taxonomic notes, lectotype designations and new synonymies in some species of the bee genus Centris Fabricius, 1804 described by Sándor Mocsáry and Heinrich Friese (Hymenoptera: Apidae) - Vivallo, Felipe (Zootaxa, 2019)
In this paper some primary types of Centris bees described by Sándor Mocsáry and Heinrich Friese deposited at Magyar Természettudományi Múzeum, Hungary were studied. To stabilize the application of some names, lectotypes were designated for C. aeneiventris Mocsáry, C. bicornuta Mocsáry, C. flavilabris Mocsáry, C. fulviventris Mocsáry, C. lineolata castaniventris Mocsáry, C. zonata Mocsáry, C. labiata Friese, C. klugii Friese, and C. fusciventris scutellata Friese. In addition, C. aeneiventris, C. intermixta Friese and C. pseudoephippia Friese are proposed as new junior synonymies of C. ephippia Smith. This latter species, along with C. scutellata are transferred to C. (Melanocentris) Friese from the subgenera C. (Ptilocentris) Snelling and C. (Aphemisia) Ayala, respectively. Taxonomic notes on type material of C. bicornuta and C. conspersa Mocsáry are also provided.